Literature Review on Acute Kidney Injury as a Predictor of Discharge in Patients With Covid-19. - Villalobos, Roberto José Bonfante; Anturi, Yuliana Cuellar; Masi, Ariel Joaquin Benegas; López, Dany Marcela Montes; Castañeda, Nicolás Ardila; Blanco, Jessica Niebles; Martínez, Isnardy Rosa Gómez; Guevara, Daniel Andres Ricardo (Jour Med Resh and Health Sci, 2022)
Coronaviruses (CoV) are single-stranded positive-sense RNA viruses, capable of rapid mutation and recombination, this is an extensive group of viruses that has been known for a long time, however, in recent years the appearance of a new member , known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19) has quickly become a pandemic that, to date, has affected millions of people in everyone. In addition, authors report that a large proportion of affected patients have underlying comorbidities that can cause greater severity in the manifestations of this pathology and can trigger complications such as acute kidney injury, which is one of the most important complications of COVID-19 to the point of being able to predispose the medical discharge of the patient as well as its mortality.